Управління логістикою в різнорідних транспортних мережах - Федорович, Олег Євгенович; Єременко, Наталія Валентинівна (НТУ "ХПІ", 2015)
Вирішено завдання побудови методів і моделі інформаційної технології логістичного управління вантажопотоками в різнорідних транспортних мережах при формуванні складних каналів доставки вантажів. Запропоновано метод розрахунку основних показників вантажоперевезень. Описано модель управління вантажоперевезеннями з використанням фракталів і агентного моделювання. Запропоновано послідовність формування фрактальної моделі управління. Побудовано архітектуру прикладної інформаційної технології логістичного управління вантажоперевезеннями.

Formulated and solved an actual scientific and applied task of methods and model building of information technology of cargo management in a products supply and marketing logistics system in geographically dispersed participants in the supply chain, as well as the complex channels of delivery in a heterogeneous transport network. Was developed the method for forming the structure of the supply and marketing chain in diverse transport network, which, unlike the existing ones, takes into account a variety of storage places, distribution centers and transshipment points and is based on the integrated use of cluster analysis, multi-criteria optimization, fuzzy logic and enumeration theory, which improves the efficiency of logistics freight management. A method for calculating the basic characteristics of freight using multiphase simulation model that takes into account the intensity of freight traffic in the distribution centers and the availability of additional transshipment points in a heterogeneous transport network that allows justifying the costs associated with loading and warehousing is offered. Described the model of freight management using fractals and agent-based modeling, the composition (the system organization) and set the control algorithm system. Proposed formation sequence of the control fractal model in which the hierarchy corresponds to the hierarchy of the fractal logistics chain. Formed an architecture of applied information technology of distributed supply chain and marketing logistics management, which consists of the following components: a block of modeling the delivery channels structure; discrete event simulation block; agent-based modeling block.
Logistic management in heterogeneous transport networks
Keywords: мультимодальні вантажоперевезення; пункт перевалки; управління збутом; фрактали; інформаційна технологія; multimodal freight; transshipment point; warehousing; sales management